**Directions(1-10):** Find the values of x and y, compare and choose a correct option.

- I.x^2 – 9x + 20 = 0

II.y^2 – 7y + 12 = 0

y > xx > yNo relationx >= yy >= xOption D

I.x^2 – 9x + 20 = 0

=>x^2 – 5x – 4x +20 = 0

=>(x-4)(x-5) = 0

=>x = 4,5

II.y^2 – 7y + 12 = 0

=>y^2 – 4y – 3y + 12 =0

=>(y-3)(y-4) = 0

=>y = 4,3

x >= y - I.x^2 – 16x +63 = 0

II.y^2 + 11y + 24 = 0

y > xy >= xx > yNo relationx >= yOption C

I.x^2 – 16x +63 = 0

=>x^2 -9x -7x+63 =0

=>(x-9)(x-7) = 0

=>x= 7,9

II.y^2 + 11y + 24 = 0

=>y^2 +8y +3y + 24= 0

=>(y+8)(y+3) = 0

=>y = -3,-8

x > y - I.4x + 3y = 21

II.5x – 2y = 9

x >= yNo relationy >= xx > yy > xOption B

On solving both the equations, we get

x =y = 3

No relation - I.x^2 +33x + 272 = 0

II.y^2 + y – 306 = 0

y >= xNo relationx >= yx > yy > xOption B

I.x^2 +33x + 272 = 0

=>x^2 + 17x + 16x + 272 = 0

=>(x+17)(x+16) =0

=>x = -17,-16

II.y^2 + y – 306 = 0

=>y^2 + 18y – 17y -306= 0

=>(y+18)(y-17) = 0

=>y = -18,17

No relation - I.2x^2 = 11x – 15

II.2y^2 = y + 10

y > xx >= yy >= xNo relationx > yOption B

I.2x^2 = 11x – 15

=>2x^2 – 6x – 5x + 15= 0

=>(2x -5)(x -3) = 0

=>x = 3,5/2

II.2y^2 = y + 10

=>2y^2 -5y +4y -10 =0

=>(y+2)(2y-5) = 0

=>y = -2,5/2

x >= y - I.x^2 – 16 = 0

II.y = (16)^1/2

y > xx > yy >= xx >= yNo relationOption C

I.x^2 – 16 = 0

=> x = -4,+4

II.y = (16)^1/2

=> y = 4

y >= x - I.x^2 – x – 6 = 0

II.y^2 + y – 6 = 0

y > xx > yy >= xNo relationx >= yOption D

I.x^2 – x – 6 = 0

=>x^2 + 2x – 3x -6 = 0

=>(x +2)(x-3) = 0

=>x = 3,-2

II.y^2 + y – 6 = 0

=>y^2 +3y – 2y – 6 = 0

=>(y+3)(y-2) = 0

=>y = -3,2

No relation - I.x + y = 9

II.2x – y = 6

y >= xx >= yy > xx > yNo relationOption D

On solving both the equations, we get

x = 5

y = 4

x > y - I.x^2 + 13x +36 = 0

II.y^2 + 15y + 56 = 0

y > xx >= yx > yNo relationy >= xOption D

I.x^2 + 13x +36 = 0

=> x^2 + 9x + 4x + 36 = 0

=>(x+9)(x+4) = 0

=>x = -9,-4

II.y^2 + 15y + 56 = 0

=>y^2 + 8y + 7y + 56 = 0

=>(y+8)(y+7) = 0

=> y = -8,-7

No relation - I.x^2 +5x +6 =0

II.y^2 + 2y – 8 = 0

y >= xy > xx >= yx > yNo relationOption E

I.x^2 +5x +6 =0

=>x^2 + 2x + 3x + 6 = 0

=>(x+2)(x+3) = 0

=>x = -2,-3

II.y^2 + 2y – 8 = 0

=>y^2 + 4y – 2y – 8 = 0

=>(y+4)(y-2)=0

=>y = -4,2

No relation